Case report: A case of giant accessory hepatic lobe torsion combined with left hepatic vein branch thrombosis in a child - Xiong, Xiangang; Lou, Yonghua; Zhou, Teng; Zheng, Zebing; Liu, Yuanmei; Liu, Rui; Zhang, Kaizhi; Gong, Yuan; Tang, Chengyan; Jin, Zhu (Frontiers in Pediatrics, 2022)
The accessory hepatic lobe (AHL) is a rare congenital malformation of the hepatic tissue, among which the giant AHL is the rarest in children. Patients without complications are usually asymptomatic, and the most auxiliary examinations cannot provide a definitive preoperative diagnosis. Surgical procedure is the only recommended management for patients who suffered from the complications of AHL. We report the case of a rare pediatric giant AHL torsion combined with left hepatic vein branch thrombosis which was successfully treated by laparoscopic lobectomy followed by excision of AHL.